Capacidades estatais, trabalho e seguridade social: África do Sul, Argentina e Brasil em perspectiva comparada - Arnaldo Provasi Lanzara (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This study analyzed in comparative perspective the social protection systems in South Africa, Argentina and Brazil, highlighting the different levels of existing links between their security policies and labor protection. The study compared the state capacity to implement social policies of these countries and their constraints in achieving the objectives of economic growth with social protection. It is concluded that the main differences between their countries stem from their different public policies and protection strategies for tackling social problems, especially in times of economic growth. In the cases of Argentina and Brazil, protection strategies are focused on the generation of formal employment, emphasizing the increased capacity of the respective States to provide contributory benefits and increasing labor protection and the minimum wage. In contrast, in South Africa there is a disjunctive between social security and protection of labor, which in addition to absent of state support have a marked privatizing character.
Keywords: J48; J88; J32; 330; state capacities; labour; social security; South Africa; Argentina; Brazil